2022
DOI: 10.1007/s44229-022-00021-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Schistosomiasis and Associated Risk Factors Among Primary School Students in the Zaki Local Government Area, Bauchi State, Nigeria

Abstract: Urinary schistosomiasis, a water-based disease, is endemic to Nigeria. The infection is transmitted by trematodes known as Schistosoma haematobium. The goal of this study was to determine the occurrence of urinary schistosomiasis among primary school children in the Zaki Local Government Area, Bauchi State, Nigeria. A cross-sectional study involving 300 school pupils from three primary schools in Zaki was conducted between June and November of 2021. The urine samples were examined with the sedimentation techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…There is significant association of infection with S. haematobium and the primary school the pupils attended with the highest prevalence of 20.8% found at NSUK Demonstration School than others primary schools. This research even though is lower in prevalence is similar to the work of Abubakar et al [16] in Kano who had high prevalence rate of infection among public primary schools compared with low prevalence rate among pupils that attended private schools. Some of the factors that made NSUK Primary school to have high prevalence rate of urinary schistosomiasis could be due to the large population density of the students who come from the surrounding communities most of whose parents are mostly farmer, traders, artisans and civil servants.…”
Section: Resultssupporting
confidence: 88%
“…There is significant association of infection with S. haematobium and the primary school the pupils attended with the highest prevalence of 20.8% found at NSUK Demonstration School than others primary schools. This research even though is lower in prevalence is similar to the work of Abubakar et al [16] in Kano who had high prevalence rate of infection among public primary schools compared with low prevalence rate among pupils that attended private schools. Some of the factors that made NSUK Primary school to have high prevalence rate of urinary schistosomiasis could be due to the large population density of the students who come from the surrounding communities most of whose parents are mostly farmer, traders, artisans and civil servants.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies had also shown that this selective approach hampers control efforts, as infected adults and adolescents serve as reservoirs for transmission to vulnerable children [ 47 , 67 , 68 ]. Additionally, the overall prevalence of UgS in comparison to other regions of Nigeria where MAMs successfully covered school-aged children (5–14 years) was lower in these studies [ 21 , 23 , 24 , 69 , 70 ]. This highlights the effectiveness of MAMs that has been ongoing in Anambra State for a decade but also underlines the necessity for a more comprehensive, long-term control strategy to achieve complete eradication.…”
Section: Discussionmentioning
confidence: 61%
“…The overall prevalence of urogenital schistosomiasis among adolescents studied in Anambra State was 14.5%, with no statistically significant difference between genders. However, adolescents aged 10–14 years exhibited the highest prevalence, which may be attributed to their increased involvement in water-related activities as adduced by previous studies [ 24 , 65 , 66 ]. This rate is notably higher compared to recent studies within Anambra State and indicates the need for revised intervention strategies [ 10 , 27 , 49 ].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These ndings emphasize the need for a holistic approach targeting females with health education, improved sanitation, clean water sources, and sexual and reproductive health services [70,71,72]. Teenagers aged 10-14 demonstrated the highest prevalence, which corresponds with their increased involvement in water-related activities [24,73,74]. Additionally, senior secondary students had higher infection rates, likely attributed to their occupations involving water contact.…”
Section: Discussionmentioning
confidence: 99%